Encouragement makes good things happen - Schoenaker, Theo J. L. (New York : Brunner-Routledge, 2010)
Describes a courageous and encouraging style of living and focuses on the belief that human encouragement is the most important natural ingredient for the healthy development of human beings. This book explores the negative consequences of discouragement on the individual and on society as a whole. It also discusses what encouragement is
1. The discouraged society -- 2. Human beings and encouragement -- 3. Encouragement -- 4. Qualities to be developed -- 5. How to encourage yourself and others -- 6. Fairy tales -- 7. Theo Schoenaker's concept of encouraging-training
Includes bibliographical references (p. 191-194) and index
Keywords: Encouragement